Presurgical Orthopedic Intervention Prior to Cleft Lip and Palate Repair: Nasoalveolar Molding Versus Passive Molding Appliance Therapy. Issue 2 (5th March 2021) - Gibson, Ella; Pfeifauf, Kristin D.; Skolnick, Gary B.; Kim, Andrew; Naidoo, Sybill D.; Snyder-Warwick, Alison; Huebener, Donald V.; Patel, Kamlesh B.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Nasoalveolar molding (NAM) is a widely used presurgical orthopedic device, despite disputes over its effectiveness. This study compares the outcomes after cleft lip and nose repair in patients who received NAM versus those who underwent passive alveolar molding with lip taping. Methods: A retrospective review of patients with complete unilateral cleft lip and palate who received either NAM ( n  = 16) or passive molding ( n  = 10) treatments was conducted. Alveolar gap width was measured on maxillary casts until time of palatoplasty. Nasolabial symmetry was assessed by examining anthropometric ratios on post-operative three-dimensional photographs. Burden of care was evaluated by analyzing the number of patient appointments attended, treatment costs, and caregiver satisfaction surveys. Results: No statistically significant difference existed in alveolar gap at time of initial appointment or palatoplasty, however the gap was smaller in the NAM cohort at time of lip and nose repair. No statistically significant difference existed in postsurgical heminasal width, nostril width, nostril height, labial height or nasal ala projection asymmetry between the NAM and the passive molding cohort. Patients in the NAM group attended more dental appointments and incurred higher treatment costs compared to the passive molding group. Caregivers reported high satisfaction with treatment outcomes in both cohorts. Conclusions: There were no differences between NAM and passive molding regarding postsurgical nasolabial appearance and patient satisfaction. Both treatments narrow the alveolar gap. However, NAM places a higher burden of care on families.